7 - Book Reviews: Women in Tanzania: an Analytical Bibliography, by Ophelia MASCARENHAS and Marjorie MBILINYI (Scandinavian Institute of African Studies, Uppsala, 1983). - BUJRA, Janet M. (Africa Development, 1984)
Abstract